Cardiac Catheterization and Intervention in Pediatric Cardiac Disease: A Narrative Review of Current Indications, Techniques, and Complications - Bahram Pishgoo; Amin Shahmoradi; Leila Asadian (Journal of Pediatrics Review, 2017)
Context: In the past 20 to 30 years, the area of pediatric interventional cardiology has had noteworthy development. Technological revolutions have significantly progressed management of cardiovascular disease in both children and adults with congenital heart disease (CHD). This article reviews the current indications, techniques and complications of interventional therapy for CHD.